Objectives and Practices of Horse breeding in Western and Southern Darfur States - Sudan - Musa, Lutfi Mohamed-Ahmed; elajb, Mohamed-ELBadri Idriss; Ishag, Ibrahim Ali; Nour, Ikhlas Ahmed; Ahmed, Mohamed-Khair Abdalla; Omer, Romaz Mohammed Ahmed (Journal of Veterinary Medicine and Animal Production, 2021)
This study was performed to generate base-line information on the goals and practices of horse breeding in Western and Southern Darfur States using a structured questionnaire and observations to collect information from a total of 200 horse owners in both states in one visit interviews. The results indicated a significant proportion of illiterates among the horse owners. Horses were important as a source of income generation as one third of owners obtained their cash from raising them. The majority of horse owners keep only males horses and the average herd size found was quite small (1.61 ± 0.98 heads). Horses play multi-functional roles in their production systems; racing, riding and work were approximately equally important. The majority of horse owners (48%) obtained their replacements through purchasing from commercial herds. Almost all respondents adopted natural mating, but the mating was controlled in 55% and haphazard in 45% of the herds. Plans aiming at genetic improvement of the horses were totally absent in the areas neither by the owners nor by the relevant institutions. The majority of horse owners particularly, those who breed horses for racing and riding purposes were interested in improving their animals by crossbreeding using the available European stallions in the horse improvement centers in Darfur. On the other hand, 55% of the respondents reported prevalence of diseases specially, viral and bacterial ones and feed deficiency in terms of quality and quantity during the last 12 months preceding the survey. The horse owners stressed that the Darfur conflict and water shortage were very important constraints also. Clearly, more research is needed in order to design sustainable programs for improving and utilizing the Sudanese horse populations. Finally this study recommends establishment of horse research centers in some parts of the country, specially, in Darfur.